3WCC Temperature Integration in a Gasoline-HEV Optimal Energy Management Strategy. (12th February 2014) - Michel, Pierre; Charlet, Alain; Colin, Guillaume; Chamaillard, Yann; Nouillant, Cédric; Bloch, Gérard
Abstract : For a gasoline-hybrid electric vehicle (HEV), the energy management strategy (EMS) is the computation of the distribution between electric and gasoline propulsion. Until recently, the EMS objective was to minimize fuel consumption. However, decreasing fuel consumption does not directly minimize the pollutant emissions, and the 3-way catalytic converter (3WCC) must be taken into account. This paper proposes to consider the pollutant emissions in the EMS, by minimizing, with the Pontryagin minimum principle, a tradeoff between pollution and fuel consumption. The integration of the 3WCC temperature in the EMS is discussed and finally a simplification is proposed.